Office Ergonomics Challenges and Strategies to Enhance The Productivity of FKIP UKSW Administrative Staff - Mara Jatiindra Abhioga; Tri Nugroho Budi Santoso; Dwi Iga Luhsasi (Jurnal Administrasi Bisnis, 2026)
This study aims to describe employees' understanding of ergonomics, identify the challenges of applying ergonomics, and formulate office ergonomics strategies to improve the work productivity of administrative staff at FKIP UKSW. A descriptive qualitative approach was used at FKIP UKSW with administrative staff as the main informants and faculty leaders and service users as supporting informants. Data were collected through interviews, observation, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldana through data reduction, data display, and conclusion drawing/verification. Data validity was strengthened through source and technique triangulation. The results show that employees' formal understanding of ergonomics remains low and is mostly obtained independently. The main challenges include non-ergonomic chairs, damaged hydraulic features, limited workspace, monitor glare, and the absence of standardized occupational health and safety or office ergonomics guidelines. Recommended strategies include standardizing work facilities, conducting ergonomics workshops, developing occupational health and safety procedures, implementing micro-breaks, redesigning the workspace, and strengthening workplace communication.